A Manifesto for Education (Praxis Educativa, 2018)
In November 2010 the authors finished the writing of a manifesto for education. The manifesto was an attempt to respond to a number of issues concerning education, both in the field of educational research and in the wider socio-political environment.This is the text of that manifesto followed by two commentaries in which the authors try to highlight some of the reasons that have ledto the writing of the manifesto, and in which an attempt is made to situate the manifesto in a number of discussions and debates.
Keywords: education; educational investigation; democracy; resistance; fight